2002
DOI: 10.1021/jo016159r
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid Promoted Cyclization of Enyne Triesters and Diesters

Abstract: Reactions of enynes with three or two ester groups (1-4) in the presence of halogen-ligand Lewis acids gave cyclized products with halide incorporation (5-8) with high generality. The cyclization process was also analyzed in a theoretical study. Facile isomerization and dehydrohalogenation of five-membered products 5 and 8 by Al(2)O(3) or Et(3)N were also observed; this process introduces conjugated moieties into the products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…[17] Later on, Yamazaki, Yamabe and co-workers carried out extensive work on this metal halide promoted intramolecular cyclizations of enyne diesters/triesters. [18,19] Yamazaki et al reported an elegant intramolecular cycloisomerization of enyne triester of type 3 to compound 4 using stoichiometric amount of ZnBr 2 as the promoter and THF as an additive (Scheme 1b). [20] Recently, Novikov, Tomilov and co-workers demonstrated a new synthetic concept of utilizing dialkyl 2-arylidene malonates as 1,2zwitterionic synthons [21] in the presence of stoichiomet-ric amount of gallium halides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Later on, Yamazaki, Yamabe and co-workers carried out extensive work on this metal halide promoted intramolecular cyclizations of enyne diesters/triesters. [18,19] Yamazaki et al reported an elegant intramolecular cycloisomerization of enyne triester of type 3 to compound 4 using stoichiometric amount of ZnBr 2 as the promoter and THF as an additive (Scheme 1b). [20] Recently, Novikov, Tomilov and co-workers demonstrated a new synthetic concept of utilizing dialkyl 2-arylidene malonates as 1,2zwitterionic synthons [21] in the presence of stoichiomet-ric amount of gallium halides.…”
Section: Introductionmentioning
confidence: 99%
“…showed that in the presence of stoichiometric amount metal halide containing nucleophilic ligand such as FeCl 3 , enyne triester of type 1 undergoes intramolecular cyclization to compound 2 (Scheme 1a) [17] . Later on, Yamazaki, Yamabe and co‐workers carried out extensive work on this metal halide promoted intramolecular cyclizations of enyne diesters/triesters [18,19] . Yamazaki et al.…”
Section: Introductionmentioning
confidence: 99%
“…Snider and Roush reported that Lewis acid-promoted intramolecular reactions of alkenyl and alkynyl ethenetricarboxylates gave chlorinated γ-lactones. 9 We have developed Lewis acid-promoted stereoselective cyclization of alkynyl ethenetricarboxylates with high generality 10 and Lewis acid-promoted 3,4-trans stereoselective cyclization of alkenyl ethenetricarboxylates has also been investigated (eqn (1)). 11 ð1Þ…”
Section: Introductionmentioning
confidence: 99%
“…(1). 4 As part of our efforts to demonstrate the scope and limitations of this Lewis acid-promoted enyne cyclization, heteroatom substituted substrates are attractive, due to further synthetic utility of the products. It is also of mechanistic interest to examine the effect of substituents on the acetylene and malonate moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Enynes 3 bearing silicon substituents on the alkyne are expected to have different reactivity to alkyl or aryl acetylenes, since a vinyl cation intermediate is involved in the previously proposed mechanism. 5, 4 Phosphonate groups are expected to have high reactivity, comparable to malonate groups. 6 The synthetic potential for compounds bearing heteroatoms such as silicon and phosphorus is also well recognized.…”
Section: Introductionmentioning
confidence: 99%